2017
DOI: 10.1002/eap.1620
|View full text |Cite
|
Sign up to set email alerts
|

What mediates tree mortality during drought in the southern Sierra Nevada?

Abstract: Severe drought has the potential to cause selective mortality within a forest, thereby inducing shifts in forest species composition. The southern Sierra Nevada foothills and mountains of California have experienced extensive forest dieback due to drought stress and insect outbreak. We used high-fidelity imaging spectroscopy (HiFIS) and light detection and ranging (LiDAR) from the Carnegie Airborne Observatory (CAO) to estimate the effect of forest dieback on species composition in response to drought stress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 74 publications
(136 reference statements)
4
52
0
Order By: Relevance
“…Among the drought's many effects was the initiation of a severe tree mortality event (Paz‐Kagan et al. , Preisler et al. , Young et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the drought's many effects was the initiation of a severe tree mortality event (Paz‐Kagan et al. , Preisler et al. , Young et al.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality triggered by the 2012–2016 drought was concentrated in pines (particularly ponderosa pine), drier locations (generally lower elevations and latitudes), and larger trees (Paz‐Kagan et al. , Preisler et al. , Young et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Requisite to the identification of drought refugia is the resolution of spatial and temporal indicators of drought‐induced biological response. Early efforts linking meteorology with forest response have included spatially explicit but temporally static relationships (Paz‐Kagan et al, ; Young et al, ) or temporally dynamic but spatially limited relationships (Bell et al, ; Chen et al, ). The simultaneous examination of vegetation response to drought through both time and space requires a robust indicator of forest physiological response to drought.…”
Section: Introductionmentioning
confidence: 99%
“…, Guarín and Taylor , Paz‐Kagan et al. ). A small number of studies in tropical forests have found more severe drought impacts in drier topographic positions (Nishimua et al.…”
Section: Introductionmentioning
confidence: 99%